A6.02 Somatic mutations in clonally expanded CD8+ T cells in patients with newly diagnosed rheumatoid arthritis. (24th February 2016) - Kelkka, T; Savola, P; Rajala, H; Kuuliala, A; Kuuliala, K; Eldfors, S; Ellonen, P; Lagström, S; Khajuria, RK; Jaatinen, T; Koivuniemi, R; Repo, H; et al.
Abstract : Background and objectives: Clonally expanded CD8 + lymphocytes are known to exist in patients with rheumatoid arthritis (RA). Interestingly, in large granular lymphocyte (LGL) leukaemia (a haematological malignancy with indolent disease course), CD8 + lymphocytes expand and the expanded clones harbour somatic mutations. LGL leukaemia patients with STAT3 mutated CD8 + lymphocytes have significantly increased risk of developing autoimmune manifestations, RA being a common autoimmune co-morbidity. As somatic mutations in CD8 + lymphocytes associate with autoimmunity in LGL leukaemia, we wanted to examine if similar phenomenon exists in newly diagnosed RA patients without known LGL lymphoproliferation. Materials and methods: Lymphocyte clonality was analysed by flow cytometry using vbβ -staining kit (Beckman Coulter) and the major clones were confirmed by TCR deep sequencing. Deep sequencing of 986 selected immune-related genes was performed from CD8 + T cells using CD4 + lymphocytes as germline control. The coverage was 200–6000x enabling reliable calling of low frequency mutations. Candidate mutations were validated using targeted deep amplicon sequencing. Results: 43% (n = 31) of the newly diagnosed RA patients in our patient cohort (n = 68) had CD8 + lymphocyte expansions exceeding 10% of the total CD8 + T cells. The largest clones were subjected to targeted deep sequencing. We identified somatic gene variants in five (n = 5) patients and in one healthy control. Most of these variants were non-synonymous coding single nucleotide changes in genes important for immune functions ( C5, PADI4, IRF1, SLAMF6, BST1 and CLEC10A ), or proliferation ( PTPRO, PADI4, PROM1, CDK12 and CLIP2 ). Sequencing of FACS sorted CD8 + lymphocytes confirmed that the expanded clone harboured the identified mutations. Conclusions: In RA patients, somatic mutations accumulate in the CD8 + T cells during clonal expansion. Related findings have recently been reported in the myeloid lineage, where somatic variants are found to accumulate even in healthy subjects in a process called clonal haematopoiesis. Importantly, we focused on CD8 + lymphocytes that have undergone thymic education and thus we report acquired somatic variants in mature cytotoxic lymphocytes in a non-malignant set-up. Although more research is needed to address the possible pathogenicity of the identified mutations, these findings provide an interesting link between autoimmunity and cancer.